The incidental capture of sea turtles in fishing gear in Terengganu, Malaysia - Chan, Eng Heng; Liew, Hock Chark; Abd. Ghaffar, Mazlan (Elsevier, 1988)
Data derived from interviews with fishermen revealed that incidental captures of sea turtles in fishing gear contribute significantly to the mortality of these animals in Terengganu, Malaysia. Trawl nets were mainly involved, with drift/gill nets and bottom longlines also capturing appreciable numbers of turtles. It was estimated that trawl and drift nets each had the potential of capturing an average of 742 and 422 turtles, respectively, per year. A large number of the turtles caught were leatherbacks Dermochelys coriacea, followed by both olive ridleys Lepidochelys olivacea and green turtles Chelonia mydas. No hawksbill Eretmochelys imbricata captures were recorded. Turtles caught in trawl nets were usually dead when landed, while drift/gill net and bottom longline captures had some chances of survival. The problem of squid jigging is also discussed. Methods for reducing the deleterious effects of fishing gear are presented.